Advances in Dye Removal Technologies - Mondal, Sourav; Purkait, Mihir Kumar; De, Sirshendu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book describes the various advanced treatment methods for removal of multiple types of dyes from effluent stream. It pays particular attention to the economic aspects of treatment of textile waste-water. The different technologies illustrated in the book include adsorption, nanofiltration, advanced oxidation, micellar enhanced ultrafiltration, cloud-point extraction, and electrocoagulation. The book presents in-depth analyses of the removal mechanisms and performance optimization of the processes involved therein. This book will be useful to chemists, chemical engineers, environmental engineers, and health and pollution control professionals. The contents have been presented in a manner that they can be easily understood and applied by a wide variety of readers including researchers, students, and practicing engineers.
Introduction -- Adsorption of Dyes -- Adsorption of Dyes From Effluent -- Surfactant Enhanced Carbon Regeneration -- Nanofiltration of Dyes -- Hybrid Treatment Method of Industrial Effluent (ADS+NF and AOP+ NF) -- Micellar Enhanced Ultrafiltration of Dye -- Cloud Point Extraction (CPE) -- Electrocoagulation -- Emulsion Liquid Membrane.
Keywords: Chemistry, Technical; Water; Hydrology; Environmental chemistry; Industrial Chemistry; Water; Environmental Chemistry